Health informatics. Identification of medicinal products. Implementation guidelines for ISO 11239 data elements and structures for the unique identification and exchange of regulated information on pharmaceutical dose forms, units of presentation, routes of administration and packaging. (18th April 2023) - British Standards Institution,
No abstract available